Variation in the TAS1R2 Gene, Sweet Taste Perception and Intake of Sugars - Dias, Andre G.; Eny, Karen M.; Cockburn, Moira; Chiu, Winnie; Nielsen, Daiva E.; Duizer, Lisa; El-Sohemy, Ahmed (Journal of nutrigenetics and nutrigenomics, 2015)
Background/Aims: To determine whether variation in the TAS1R2 gene affects sucrose taste perception and sugar intake. Methods: Participants were men (n = 238) and women (n = 458) aged 20-29 years. A subset (n = 95) with body mass index (BMI) data available completed a sensory analysis study. A food frequency questionnaire assessed dietary intake, and eight polymorphisms were genotyped (rs12033832, rs12137730, rs35874116, rs3935570, rs4920564, rs4920566, rs7513755 and rs9701796). Sucrose taste thresholds were determined by staircase procedure (solutions: 9 × 10 -6 to 0.5 mol/l). Suprathreshold sensitivity to 0.01-1.0 mol/l sucrose solutions was assessed using general Labeled Magnitude Scales. Results: A significant genotype-BMI interaction was observed for rs12033832 (G>A) for suprathreshold sensitivity (p = 0.01) and sugar intake (p = 0.003). Among participants with a BMI ≥25, G allele carriers had lower sensitivity ratings (mean incremental area under the taste sensitivity curve ± SE; GG/GA 54.4 ± 4.1 vs. AA 178.5 ± 66.6; p = 0.006), higher thresholds (GG/GA 9.3 ± 1.1 vs. AA 4.4 ± 4.3 mmol/l; p = 0.004) and consumed more sugars (GG/GA 130 ± 4 vs. AA 94 ± 13 g/day; p = 0.009). G allele carriers with a BMI <25 had lower thresholds (GG/GA 8.6 ± 0.5 vs. AA 16.7 ± 5.7 mmol/l; p = 0.02) and consumed less sugars (GG/GA 122 ± 2 vs. AA 145 ± 8 g/day; p = 0.004). Conclusion: The rs12033832 single nucleotide polymorphism in TAS1R2 is associated with sucrose taste and sugar intake, but the effect differs depending on BMI.